PENGARUH LAMA PENGERINGAN TERHADAP KARAKTRISTIK SIFAT KIMIA COOKIES TEPUNG KACANG TUNGGAK (Vigna unguiculata L) - Sriwahyuni Nur; Muhammad Wiharto Caronge; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to determine the effect of  long as drying on the characteristics of the chemical nature of cookies flour cowpea  (Vigna unguiculata) and to know the level of panelists acceptance of  the it cookies flour cowpea . This research is a quantitative research (experiment) which is done with two stages, namely the process of making flour  cowpea and making of cookies flour cowpea. This study used Completely Randomized Design (RAL) with variation of P, Q and R drying  time of each 2 hours, 4 hours and 6 hours with rendamen observation, moisture content, ash content, protein content, protein content, carbohydrate and sensory test of cookies flour cowpea. Research data obtained by technique questionnaire and observation. Data were analyzed by  used  variance analysis technique (ANOVA) continued  by DMRT test (duncan) and one sample test. The results showed that the best drying treatment was 4 hours with 46.8% rendamen, water content 9.85%, ash content 3,71%, protein content 26,84% and carbohydrate 57,54%.